The Relationship Between Helminthiasis and Nutritional Status in Children - Maryam, Andi; Elis, Andi; Fatma A (Fakultas Kedokteran, Universitas Papua, 2025)
Helminthiasis remains a prevalent public health problem in Indonesia, particularly among elementary school-aged children who are vulnerable to infection due to poor environmental sanitation and inadequate hygiene practices. This study aims to analyze the relationship between helminthic infection and nutritional status among students at SDN Polenga Jaya, located in the working area of the Poli-Polia Public Health Center. This research employed a quantitative analytic method with a cross-sectional design and involved 32 respondents selected through total sampling. Data were collected through interviews, stool examinations to detect helminth eggs, and nutritional status assessment using the Body Mass Index-for-Age (BMI-for-age) index. Bivariate analysis using the Chi-square test indicated a significant association between helminthic infection and nutritional status (p = 0.012; α = 0.05). Conclusion: Children infected with helminths tend to have lower nutritional status compared to those who are not infected. Therefore, interventions through education, promotion of clean and healthy living behaviors, and regular health screenings are necessary to prevent helminthic infections and maintain optimal nutritional status in children.